Respuestas
Respuesta dada por:
1
Respuesta:
-3×(4-6)-2×{5×[3-5×(-7+5)-3]}=
-3×(-2)-2×{5×[3-5×(-2)-3]}=
6-2×{5×[3-(-10)-3]}=
6-2×{5×[3+10-3]}=
6-2×{5×[13-3]}=
6-2×{5×[10]}=
6-2×{5×10}=
6-2×{50}=
6-2×50=
6-100=
-94
Respuesta dada por:
0
Explicación paso a paso:
−3(4−6)−2(5(3−5(−7+5)−3))
=(−3)(−2)−2(5(3−5(−7+5)−3))
=6−2(5(3−5(−7+5)−3))
=6−2(5(3−(5)(−2)−3))
=6−2(5(3−(−10)−3))
=6−2(5(13−3))
=6−2(5)(10)
=6−(2)(50)
=6−100
=−94
espero que te sirva
Preguntas similares
hace 2 años
hace 5 años
hace 5 años
hace 5 años